Adolescents' response to parental Facebook friend requests: The comparative influence of privacy management, parent-child relational quality, attitude and peer influence. (July 2016) - Mullen, Caron; Fox Hamilton, Nicola
Abstract: Smartphones greatly reduce parents' ability to monitor their children's online activities. A recommended surveillance technique is to 'friend' adolescents on social networking sites (SNS) such as Facebook. However, adolescents use these sites to experiment with adjusting their self-image based on friends' feedback, so is it possible for them to simultaneously satisfy the very different expectations of both peers and parents? This study explores adolescents' attitudes to parental presence on Facebook using Communications Privacy Management theory (Petronio, 2002) as the theoretical framework to investigate the relative influence of privacy management, relational quality and peer pressure. The study was conducted among 262 secondary school children living at home and recruited via their schools. Results showed that while privacy management and peer influence were significantly related to adolescent attitudes to parental presence on Facebook, only attitude to parental presence on Facebook and parental-adolescent relational quality predicted friendship status. A picture emerged of adolescents very much in control of their SNS privacy who were largely indifferent to parents on Facebook. There was however, a sizable, peer-influenced minority, opposed to parental presence, for whom friendship may be counter-productive. While this study uncovered many unique associations relating to adolescent-parental Facebook friendship, further qualitative research is recommended to provide a deeper understanding of this complex subject. Highlights: Majority of adolescents indifferent to parental presence on Facebook. Parental 'friending' potentially counter-productive for strongly opposed minority. Evidence that strict privacy management practices prevail. 84% of adolescents have 3–7 different SNS accounts. Majority use Messenger for chatting to maintain greater control of their privacy.